Disability profile of grant recipients in a semi-rural area in South Africa - A. Frieg (South African Journal of Physiotherapy, 2001)
A descriptive study was undertaken to establish, amongst others, the demographic details and the disability profile of a group of persons with disabilities who collected their disability grant at the Kleinmond Post Office in June 1999. Data were collected by means of a questionnaire during face-to-face interviews with the grantees and/or their proxies. A questionnaire developed for this purpose included a disability catalogue based on the International Classification of Impairments, Disabilities and Handicaps (ICIDH). The repeatability of the questionnaire was 96%. The mean age of the mainly male grantees was 42 years (range: 18-64). Nearly a third of the subjects had been disabled since birth, reinforcing the importance of disability prevention programmes as outlined in several policy documents. Most persons with disabilities had problems with activities in the situational disability category (82% or 24/29), while only a few reported personal care disabilities (34% or 10/29). The majority of the grantees (86% or 25/29) reported disabilities in more than one category. This may be an indication that only persons with multiple disabilities qualify for permanent disability grants in South Africa.